Father Knows Best - Judith Roof (Studies in 20th & 21st Century Literature, 1994)
In his essay, "Althusser's Mirror," Carsten Strathausen reveals the paternal politics inherent to any gesture of appropriation. Molding Lacan to an Althusserian mirror, Strathausen demonstrates parallels between Lacan's mirror stage and Althusser's interpellated subject. The resemblance, created through what Strathausen suggests is Althusser's mis-reading of Lacan, reveals their mutual influence. The question of influence, however, becomes an issue of tradition Althusser links to a politics of legitimacy and right he associates with a figure of paternity. While the process of filiation would seem to extend from Lacan to Althusser in the logic of the mirror employed by Strathausen to renew Marxist thought, Althusser also situates himself as the father to a Lacan he is attempting to salvage from the ignominy of illegitimacy.
Keywords: Carsten Strathausen; paternal politics; patriarchy; appropriation; Lacan; Althusser& #x27; s Mirror; essay; paternity